2017
DOI: 10.1126/sciadv.1700738
|View full text |Cite
|
Sign up to set email alerts
|

Confining metal-halide perovskites in nanoporous thin films

Abstract: In situ perovskite nanocrystal formation within nanoporous thin films allows emission color tuning in optoelectronic devices.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
145
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(149 citation statements)
references
References 67 publications
4
145
0
Order By: Relevance
“…It was reported that the energy spectrum of an emissive compound became discrete as its dimension was reduced to nanoscale (tens nanometer). Consequently, not only the resulting bandgap was size‐dependent but also the photoluminescence (PL) would be blue‐shifted and intensified with the decrease of the nanocrystal's size, known as the quantum confinement . Thus far, versatile methods have been explored to modulate the nanostructure of perovskite materials, especially by means of controlling the stoichiometry of the perovskite precursors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that the energy spectrum of an emissive compound became discrete as its dimension was reduced to nanoscale (tens nanometer). Consequently, not only the resulting bandgap was size‐dependent but also the photoluminescence (PL) would be blue‐shifted and intensified with the decrease of the nanocrystal's size, known as the quantum confinement . Thus far, versatile methods have been explored to modulate the nanostructure of perovskite materials, especially by means of controlling the stoichiometry of the perovskite precursors.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Zhang et al revealed that a ligand‐assisted reprecipitation technique, wherein the n ‐octylamine and oleic acid were added into the perovskite precursor solution as surfactants, can enhance the PL intensity and PLQY (to 70%) of CH 3 NH 3 PbBr 3 . Very recently, Kaltenbrunner et al employed nanoporous alumina or silicon as a scaffold to regulate the shape/size of the nanocrystalline perovskite (less than 10 nm) to exhibit conspicuous quantum size effects. Despite such achievements, the researchers are still seeking a facile method exempting from tedious purification or post‐treatment to prepare the perovskite materials, which is beneficial for the widespread applications of perovskite materials in the optoelectronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…[40] Employing nanoporous alumina (npAAO) matrixes, the perovskite nanocrystals were formed in a manner similar to the other two approaches (Figure 2i). Pores were only partially filled, as visualized with scanning TEM (STEM), with sphericallike perovskite NCs clearly visible, even in the rod-like pores of the npAAO (Figure 2j,k).…”
Section: Template-assisted Fabricationmentioning
confidence: 84%
“…Indeed, peak broadening has been observed for 8.4 nm cubic perovskite nanocrystals or in perovskite nanocrystallites synthesized in the confined geometry of porous Si wafers. [33,40] For anisotropic particles, a more careful analysis is needed. For example, several groups have successfully synthesized nanoplatelets in the cubic phase.…”
Section: Characterization Methodsmentioning
confidence: 99%
“…However, the applications of CsPbX 3 , including solar cells, lasers, and displays, are inhibited because of their unstable nature under an oxide and humid atmospheric environment. To improve the stability of CsPbX 3 nanocrystals, one of the efficient approaches is to incorporate them into inert host matrices, such as organic polymers and inorganic glasses …”
Section: Introductionmentioning
confidence: 99%